Methodology of the 2016 RAND Presidential Election Panel Survey (PEPS) - Pollard, Michael (RAND Corporation, 2016)
The 2016 RAND Presidential Election Panel Survey uses the American Life Panel (ALP) to study voting intentions, public opinion, and voter behavior. This document provides a detailed description of our methodology.